2016
DOI: 10.1002/micr.30138
|View full text |Cite
|
Sign up to set email alerts
|

Upper and lower extremity reconstructive applications utilizing free flaps from the medial genicular arterial system: A systematic review

Abstract: MGA free flaps are a versatile option for upper and lower extremity osseous reconstruction, offering high rates of union with minimal complications for a complex patient population. This study furthers our understanding of patient outcomes following MGA flap reconstruction, which previously was limited to case reports and small case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 51 publications
(145 reference statements)
0
21
0
Order By: Relevance
“…Recent literature reports eight thumb reconstructions using the MFCF demonstrating the versatility and reliability of this flap. 18 On the distal humerus fracture, final DASH score of 0.8 demonstrates good outcomes compared with the literature (27.8), however, we are aware that this is only one case and further patients would need to be evaluated to confirm this result. Our time for consolidation after the MFCF was similar to previously published averages.…”
Section: Discussionmentioning
confidence: 67%
“…Recent literature reports eight thumb reconstructions using the MFCF demonstrating the versatility and reliability of this flap. 18 On the distal humerus fracture, final DASH score of 0.8 demonstrates good outcomes compared with the literature (27.8), however, we are aware that this is only one case and further patients would need to be evaluated to confirm this result. Our time for consolidation after the MFCF was similar to previously published averages.…”
Section: Discussionmentioning
confidence: 67%
“…Some studies showed higher complication rates (17.1% vs. 6.2%) in the lower extremities than in the upper extremities [ 38 ]. This finding could not be confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…21 Regarding MFC donor-site morbidity, Rodríguez-Vegas and Delgado-Serrano 22 reported a series of 25 patients wherein they had few transient donor-site complications, including suture intolerance, seroma, and numbness in the saphenous territory; no fracture, knee instability, or stiffness was reported. Moreover, Kazmers et al 23 performed a systematic review of 40 papers which showed that the knee donor site rate of complications was 0.8% for femoral fracture and 0.4% for persistent knee pain. As for a femoral fracture, potentially the most serious complication, two studies conducted by the same group have shown the following: first, that harvest of MFC flap sizes greater or equal than 9 cm results in significantly lower stiffness compared with the 3-cm flap while testing axial stability, however, the femur retains its axial stability even after harvest of large corticocancellous flaps from its medial aspect 24 ; on the other hand, Endara et al 25 showed that bone failure rates were 12.5, 12.5, 28.6, and 55.6% for control, 3-, 5-, and 7-cm MFC harvest size groups, respectively.…”
Section: Discussionmentioning
confidence: 99%